179k views
1 vote
How to do step by step

How to do step by step-example-1
User Gerry Coll
by
5.4k points

2 Answers

0 votes

Answer:

(5/7 - 1) * (2/3 + (1/6 - 1/9) * 18/5 + 1/15) - (2/7 + 1/3) * (-7/13)

= (5/7 - 7/7) * (2/3 + (3/18 - 2/18) * 18/5 + 1/15) - (6/21 + 7/21) * (-7/13)

= (-2/7) * (2/3 + 1/18 * 18/5 + 1/15) - 13/21 * (-7/13)

= (-2/7) * (2/3 + 1/5 + 1/15) + 7/21

= (-2/7) * (10/15 + 3/15 + 1/15) + 1/3

= (-2/7) * 14/15 + 1/3

= -4/15 + 1/3

= -4/15 + 5/15

= 1/15

User Yrll
by
5.5k points
3 votes

Answer:

1/15

Explanation:

(5/7 - 1). [2/3 + (1/6 - 1/9), 18/5 + 1/15] - (2/7 + 1/3). (-7/13)

Use order of operations; PEMDAS.

Start with the inner parentheses:-

= (5/7 - 1). [2/3 + 1/18. 18/5+ 1/15] - (2/7 + 1/3). (-7/13). Now the other parentheses:-

= (-2/7). ( 2/3 + 1/5 + 1/15) - (13/21).(-7/13)

= -2/7 . 14/15 + 7/21

= -2/7 . 14/15 + 1/3

= -4/15 + 1/3

= 1/15 (answer)

User Faeeria
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.